Tingkat Adopsi Petani Terhadap Benih Padi (Oryza sativa L.) Bersertifikat dan Non-Sertifikat di Kecamatan Kalasan Kabupaten Sleman - , NOVI KUMALA DEWI, Prof. Dr. Ir. Prapto Yudono, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The use of certified seed is one of the factors that affect the increase in rice productivity. Therefore, the availability of certified seeds for farmers in farming activities is an absolute requirement. This study aims to determine the level of adoption of farmers, the level of productivity, seed quality and income levels of farmers to use certified seed paddy and non-certificate. The research was conducted in four villages namely Purwomartani, Selomartani, Tamanmartani, and Tirtomartani, Kalasan District, Sleman District, where there are farmers who use certified rice seeds and non-certificate. Techniques of data collection was done by using a questionnaire to interview farmers using certified rice seeds and non-certificate. The results of interviews processed using the Likert scoring is done. Scoring is based on the data obtained were analyzed further by t test using SPSS software version 16. The results showed that the rate of adoption of certified seed is lower than noncertified. Although productivity and farm income for certified seed were higher than noncertified. In this study, data showed that the quality for certified seed is lower than noncertified with the low quality of certified seeds to a reduction in the rate of adoption of certified seed.